Design and Fabrication of an Aerodynamic Body Kit for Formula Student Electric Vehicle (FSEV) - Khairina Batrisyia Mohd Fisal; Haszeme Abu Kasim; Hazim Sharudin; Mohd Fahmi Md Salleh; Nairul Akmar Akashah; Jason Lim Wuh Terng (Journal of Advanced Mechanical Engineering Applications, 2026)
Aerodynamic performance is an important factor to improve the efficiency, stability and handling characteristics of Formula Student electric vehicles (FSEV). However, most of the aerodynamics packages used in the Formula Student competitions relies on costly composite materials and sophisticated manufacturing processes, which are hard to implement in projects at the student level with limited financial and manufacturing resources. Therefore, this study is to design and evaluate a low-cost aerodynamic body kit for a Formula Student electric vehicle using Computational Fluid Dynamics (CFD) analysis and conventional manufacturing methods. The proposed aerodynamic package includes a streamlined nose cone, side panels, airflow channels, underbody diffuser and rear aerodynamic elements all made predominantly from aluminum material. The CFD simulations were carried out using ANSYS Fluent 2024 R1 in steady state conditions at the inlet velocities of 20 m/s, 28 m/s, 33.33 m/s and 40 m/s with the SST k-? turbulence model. The aerodynamic performance was assessed by streamline distribution, pressure contour characteristics, drag force and lift coefficient behavior. The simulation results showed that the proposed body kit reduced the drag force from 980 N to 865 N at 33.33 m/s which is approximately 11.73 % drag reduction. Also, the lift coefficient increased from ?0.74 to ?0.88, which means an increase in downforce generation and an improvement of the vehicle stability at high speeds. The optimized body geometry also avoided the separation of the air flow and minimized the formation of a wake behind the vehicle. The results indicate that a practical and cost-effective aerodynamic body kit can significantly enhance the aerodynamic performance of Formula Student electric cars without advanced manufacturing technologies.